Reperfusion strategy and late clinical outcomes of patients with ST-elevation myocardial infarction (STEMI) in the absence of standard modifiable risk factors (SMuRFs). (3rd October 2022) - Jamal, J; Idris, H; Faour, A; Yang, W; McLean, A; Burgess, S; Shugman, I; Oloughlin, A; Leung, D; Mussap, C J; Juergens, C P; Lo, S; et al.
Abstract: Introduction: There is growing evidence that patients presenting with STEMI in the absence of standard modifiable cardiovascular risk factors (SMuRFs; smoking, hypertension, hypercholesterolemia, diabetes) have poorer outcomes compared to those with atleast one SMuRF. It has been hypothesised that this may be in part due to decreased administration of pharmacotherapies in the post-infarct period due to perceived low risk. Long term outcomes of patients without SMuRFs based on reperfusion strategy received during the index admission have not been investigated. Purpose: We sought to analyse late clinical outcomes of STEMI patients with and without SMuRFs based on reperfusion strategy received during the index admission. Methods: All patients who underwent PCI between 2003 and 2014 were identified from a PCI centre STEMI database. Late clinical outcomes of patients with and without SMuRFs were analysed overall and based on reperfusion strategy [primary PCI (pPCI) vs pharmaco-invasive PCI (PI-PCI)]. Propensity matching was used to account for differences in baseline characteristics between the groups. Results: Amongst 2, 091 STEMI patients, 531 (25%) had no SMuRFs (51% pPCI, 49% PI-PCI) and 1560 (75%) had ≥1 SMuRF (52% pPCI, 48% PI-PCI). Unadjusted late mortality in SMuRF-less patients was 13.4% (18.8% pPCI, 7.7% PI-PCI) and for those with ≥1 SMuRF was 9.7% (11.0% pPCI, 8.4% PI-PCI). After propensity-matching clinical and angiographic characteristics, 5 year mortality rates were significantly higher for patients without SMuRFs compared to those with SMuRFs [HR 1.36, CI: 1.03–1.81, p=0.031]. This difference was attenuated for patients who underwent pPCI [HR 1.72, CI: 1.22–2.43, p=0.002]. Interestingly, this discrepancy was not observed amongst individuals who underwent pharmaco-invasive PCI [HR 1.13, CI: 0.53–1.48, p=0.638], as SMuRF-less patients had similar mortality rates to their counterparts. Long term rates of reinfarction, stent thrombosis and target vessel revascularisation were similar between the groups. Additionally, there was no significant difference in rates of stroke and major bleeding amongst all 4 subgroups. Conclusion: Patients presenting with STEMI in the absence of SMuRFs have increased overall late mortality compared to those with at least one SMuRF. However, this difference was not observed in patients who underwent a pharmaco-invasive strategy, whereby patients without SMuRFs had similar outcomes to those with SMuRFs after adjusting for confounders. Our findings suggest the use of a pharmaco-invasive strategy in appropriate SMuRF-less patients presenting with STEMI. Funding Acknowledgement: Type of funding sources: None.